2017
DOI: 10.1159/000469705
|View full text |Cite
|
Sign up to set email alerts
|

Cutoff Pepsinogen Level for Predicting Unintendedly Eradicated Cases of <b><i>Helicobacter pylori</i></b> Infection in Subjects with Seemingly Normal Pepsinogen Levels

Abstract: Backgrounds/Aims: In the ABC method, which is a method for risk stratification of gastric cancer using serum anti-Helicobacter pylori antibody and pepsinogen (PG) test, subjects with normal PG and seronegative for H. pylori are named as “Group A” and are regarded as having a low risk of gastric cancer. These “Group A” subjects include unintentionally eradicated cases at relatively high risk, and this study aimed to identify these subjects. Methods: Of the 109 subjects, 76 were classified as uninfected Group A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…With regard to the accuracy of HPU assessment, other reports have assessed H. pylori status by anti- H. pylori antibody, histopathology, endoscopic finding, PG test, urea breath test, rapid urease test, and/or prior H. pylori eradication [10-12]. However, a certain proportion of patients with chronic atrophic gastritis has been identified as the subjects with serum anti- H. pylori negative and PG test negative [13-14]. In this study, we assessed H. pylori status with urea breath test negative, endoscopic finding, histopathology, PG test, and anti- H. pylori antibody, as well as the absence of prior H. pylori eradication.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the accuracy of HPU assessment, other reports have assessed H. pylori status by anti- H. pylori antibody, histopathology, endoscopic finding, PG test, urea breath test, rapid urease test, and/or prior H. pylori eradication [10-12]. However, a certain proportion of patients with chronic atrophic gastritis has been identified as the subjects with serum anti- H. pylori negative and PG test negative [13-14]. In this study, we assessed H. pylori status with urea breath test negative, endoscopic finding, histopathology, PG test, and anti- H. pylori antibody, as well as the absence of prior H. pylori eradication.…”
Section: Discussionmentioning
confidence: 99%
“…There are also other issues such as the following: group A includes cases with prior or current H. pylori infection, 5 while a systematic review has shown that dividing subjects into three groups, i.e., groups A, B, and C+D, rather than four, would be more appropriate 6 . In this context, the cut‐off value and measuring method of H. pylori antibody titers, interpretation of the PG level, and cut‐off value of the PG I/PG II ratio have been investigated 7–9 …”
Section: Statement 1‐3mentioning
confidence: 99%
“…However, it is worth noting that a number of studies mentioned that gastric cancer and precancerous lesions were detected in the low risk groups of several prediction rules. [16,[20][21]. In our study, the Scoring System from JPHC identi ed the most patients as low risk (1096, 76.32%), followed by the ABC method (811, 56.48%), and Li's Scoring System (37, 37.95%).…”
Section: Discussionmentioning
confidence: 60%